O-carboxymethyl chitosan-g-cholesterol succinate monoester and preparation method and application thereof
By using O-carboxymethyl shell-G-gallol alcohol alcohol monocular ester (CCMC) as a carrier, prepare CBD/CCMC carrier nanoplasma beam, solve the problem of low CBD biological utilization, and realize the improvement of CBD water soluble The purpose of sexual and anti -inflammatory effects.
Patent Information
- Application Number
- CN202311262058.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-09-27
AI Technical Summary
The prior art is difficult to improve the bioavailability and water solubility of cannabidiol (CBD) in the body, limiting its clinical application.
By preparing O-carboxymethyl shell-G-gallol alcohol alcohol monocular ester (CCMC) as a carrier, combined with ultrasonic auxiliary self-assembly technology to form CBD/CCMC drug nano-glue beam, which significantly improves the water solution and CBD's water solution and Biological utilization.
The solubility of CBD in water has been increased, its transportation efficiency and anti -inflammatory effect in the intestine are enhanced, the retention time of drugs in the body is extended, and biological utilization is improved.
Smart Images

Figure CN117186269B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of drug-carrying nano micelles and relates to O-carboxymethyl chitosan-g-cholesterol succinate monoester and a preparation method and application thereof. Background Art
[0002] Cannabidiol (CBD), an extract of cannabis (Cannabis sativa L.), has multiple pharmacological effects, including anti-inflammatory, anti-epileptic, anti-cancer, and inhibition of coronavirus activity. [1-3] . Compared with the homologous addictive ingredient Δ9-tetrahydrocannabinol, CBD has the advantages of being non-addictive and non-psychedelic. As the medical value of CBD is gradually discovered, as of January 2019, 41 countries in the world have declared medical marijuana legal, and more than 50 countries have declared CBD legal. my country also allowed the legal cultivation of industrial hemp in Yunnan and Heilongjiang provinces in 2010 and 2018 respectively. The relaxation of policies has brought opportunities for the development of medicinal marijuana. [4] From 2018 to 2020, the United States, the European Union, and Australia successively approved the high-purity oral liquid cannabidiol preparation developed by the British GW Pharmaceuticals. Listing [5] , Sales in 2019 were $296.4 million, sparking a research boom on CBD in multiple fields.
[0003] However, CBD is a highly lipophilic compound with extremely low water solubility. Its oral bioavailability is only 6%, which is affected by its poor solubility and large first-pass effect. This limits the clinical application of CBD. [5-7] In the existing literature reports at home and abroad, there are few studies on increasing the water solubility of CBD and improving oral bioavailability. Koch et al. [8] The prepared CBD amorphous solid preparations have problems such as poor stability and low drug loading; Knaub et al. [9] A CBD self-emulsifying drug delivery system (SEDDS-CBD) was developed, which improved the oral bioavailability of CBD, but it has large individual absorption differences, complex preparations, and low safety.
[0004] As a novel form of drug encapsulation, amphiphilic nanomicelles are biocompatible and biodegradable amphiphilic block copolymers. Physical encapsulation can be used to encapsulate poorly soluble drugs, which can significantly improve the water solubility of drugs, increase safety, and have small particle size, strong tissue permeability and cell penetration, as well as the advantages of sustained and controlled release. [10-12] , which can be used as an excellent choice for CBD preparation research. The development of efficient and low-toxic amphiphilic polymers has become the primary goal of constructing CBD nanomicelle drug delivery systems.
[0005] Carboxymethyl chitosan is a safe and non-toxic natural polysaccharide derivative [13-15] It retains the bioadhesiveness and absorption-promoting properties of chitosan, contains a large number of active amino and carboxyl groups in the molecule, and its water solubility is greatly increased compared to chitosan. [16-19] After the hydrophobic block is introduced, the prepared amphiphilic polymer can form a core-shell structure nano-micelles through self-aggregation. The hydrophobic core encapsulates the hydrophobic drug (paclitaxel, etc.), and the hydrophilic shell plays a steric stabilizing role to make the micelles stably dispersed in the aqueous medium. [20-22] , thereby greatly improving the water solubility of the encapsulated drugs, prolonging the retention time of the drugs in specific parts of the body, and improving the bioavailability.
[0006] CBD is effectively loaded into amphiphilic nano-micelles, and the drug-loaded nano-micelles are prepared and then orally administered. After entering the body, it is mainly absorbed in the small intestine.
[23] . Caco-2 cells are derived from human colon adenocarcinoma cells, have a microvilli structure, and can produce enzymes related to the brush border epithelium of the small intestine. After the cells mature in culture, they can form a complete cell monolayer membrane. The structure and function are similar to those of small intestinal epithelial cells. It is internationally recognized as one of the best models for studying the absorption and transport functions of small intestinal epithelial cells. It has good stability and high reproducibility in in vitro culture. Compared with animal experiments, it is easy to operate, less time-consuming, and requires a small amount of sample. It is widely used in rapid screening of in vitro drug activity and scientific research on intestinal related issues. Therefore, it can be used as an in vitro model for the study of oral absorption of CBD amphiphilic nanomicelles.
[0007] Whether a biologically active compound can exert its effect in vivo depends largely on the drug concentration and bioavailability in plasma, and the route of administration has a significant impact on the pharmacokinetic parameters of the drug. Studies have shown that oral administration will greatly limit the oral bioavailability of CBD due to the first-pass effect, while sublingual, intravenous, and inhalation administration will reduce the absorption of CBD in the gastrointestinal tract, thereby having a significant impact on the pharmacokinetic parameters of CBD.
[24] Therefore, studying the pharmacokinetic process of CBD and two drug-loaded nanomicelles in rats after oral administration can preliminarily evaluate the difference in oral bioavailability of CBD and CBD drug-loaded nanomicelles, and provide a theoretical basis for the clinical application of CBD preparations.
[0008] Therefore, it is urgent to develop water-soluble CBD amphiphilic nanomicelles, improve the bioavailability of CBD, enhance its intestinal transport efficiency and anti-inflammatory effect, and explore the absorption and anti-inflammatory mechanism of CBD and its amphiphilic nanomicelles. This study will provide strong theoretical support for the huge development of CBD in the medical field.
[0009] References:
[0010] [1]Xu SS, Zhang H, Li CZ, et al. Cannabidiol promotes fin regeneration and reduces apoptosis in zebrafish embryos[J]. Journal of Functional Foods, 2021,86.
[0011] [2]Hotz J, Fehlmann B, Papasotiropoulos A, et al. Cannabidiol enhances verbal episodic memory in healthy young participants: A randomized clinical trial [J]. Journal of Psychiatric Research, 2021, 143: 327-333.
[0012] [3]Patel N,Kommineni N,Surapaneni SK,et al. Cannabidiol loaded extracellular vesicles sensitize triple-negative breast cancer to doxorubicin both in-vitro and in vivo models[J].International Journal ofPharmaceutics,2021,607:120943.
[0013] [4] Li Qiushi, Meng Ying, Chen Shilin. Classification and research strategy of medicinal cannabis germplasm resources[J]. China Journal of Traditional Chinese Medicine, 2019, 44(20): 4309-4316.
[0014] [5] Ning Kang, Dong Linlin, Li Mengzhi, et al. Application and development of non-psychoactive medicinal cannabis[J]. Chinese Journal of Experimental Traditional Chinese Medicine, 2020, 26(8): 228-240.
[0015] [6] Su Yanting, Cai Baoguo, Zhang Jian. Research progress of new dosage forms of cannabidiol[J]. Chinese Modern Applied Pharmacy, 2022.
[0016] [7] Ning Kang, Dong Linlin, Li Mengzhi, et al. Application and development of non-psychoactive medicinal cannabis[J]. Chinese Journal of Experimental Traditional Chinese Medicine, 2020, 26(8): 228-240.
[0017] [8]Li H,Chang SL,Chang TR,et al.Inclusion complexes of cannabidiolwithβ-cyclodextrin and its derivative:Physicochemical properties,watersolubility,and antioxidant activity[J].Journal of Molecular Liquids,2021,334:116070.
[0018] [9]Koch N,Jennotte O,Gasparrini Y,et al.Cannabidiol aqueoussolubility enhancement:Comparison of three amorphous formulations strategiesusing different type of polymers[J].International Journal of Pharmaceutics,2020,589:119812.
[0019]
[10] Knaub K,Sartorius T,Dharsono T,et al.A novel self-emulsifyingdrug delivery system(SEDDS)based on formulation technologyimproving the oral bioavailability of cannabidiol in healthy subjects[J].Molecules,2019,24(16):2967.
[0020]
[11] Li H,Chang SL,Chang TR,et al.Inclusion complexes of cannabidiolwithβ-cyclodextrin and its derivative:Physicochemical properties,watersolubility,and antioxidant activity[J].Journal of Molecular Liquids,2021,334:116070.
[0021]
[12] Li Rui, Ruan Wenhui, Yao Jun, et al. Preparation and characterization of self-assembled micelles of γ-polyglutamic acid cholesteryl derivatives[J]. Polymer Materials Science and Engineering, 2014, 30(1): 11-14. DOI: 10.16865 / j.cnki.1000-7555.2014.01.003.
[0022]
[13] Zhao W, Su L, Yu Z, et al. Improved stability and controlled release of lycopene via self-assembled micelles encapsulation[J]. LWT, 2022, 155: 112878. Wu Xiaoshan, Ni Feng, Gao Yuxuan, et al. Synthesis, characterization and anti-tumor evaluation of a novel ampelopsis derivative γ-polyglutamic acid ampelopsis ester[J]. Chinese Pharmacy, 2020, 31(22): 2720-2725.
[0023]
[14] Wu Lihao, Chen Gong, Ren Kang, et al. Research progress on degradation and metabolic behavior of carboxymethyl chitosan-based biomedical materials[J]. Polymer Bulletin, 2023, 36(02): 148-157. DOI: 10.14028 / j.cnki.1003-3726.2023.02.002.
[0024]
[15] Wang Xiao. Synthesis, preparation and performance study of novel functional modified chitosan-derivatized hydrogels[D]. Master's degree thesis]. Harbin: Harbin Institute of Technology, 2020.
[0025]
[16] Xu Feiyang. Preparation and basic application research of chitosan-based hydrogel materials[D]. Master's degree thesis]. Wuhan: Wuhan Textile University, 2021.
[0026]
[17] Wang Xiaojing. Research progress on preparation and application of carboxymethyl chitosan[J]. Chemical Engineering and Equipment, 2020, 11: 219-220.
[0027]
[18] Li Xiaoli, Shan Lu, Wang Ting, et al. Preparation and physicochemical properties of berberine / carboxymethyl chitosan-chitosan particles[J]. Journal of Weifang Medical College, 2021.
[0028]
[19] Li Ming, Liu Yang, Gong Hao, et al. Preparation and performance study of carboxymethyl chitosan composite hydrogel[J]. Chinese Journal of Marine Drugs, 2022, 41(2): 19-27.
[0029]
[20] Jin Z, Hu G, Zhao K. Mannose-anchored quaternized chitosan / thiolatedcarboxymethyl chitosan composite NPs as mucoadhesive carrier for drug delivery[J]. Carbohydrate Polymers, 2022:119174.
[0030]
[21] Pourmanouchehri Z, Ebrahimi S, Limoee M, et al. Controlled release of 5-fluorouracil to melanoma cells using a hydrogel / micelle composites based on ondeoxycholic acid and carboxymethyl chitosan[J]. International Journal of Biological Macromolecules, 2022, 206: 159-166.
[0031]
[22] Tong Xinyong, Zhou Jianping, Tan Yan, et al. Effects of carboxymethyl chitosan modification on the tissue distribution of paclitaxel self-assembled proliposomes in rats[J]. Chinese Journal of Natural Medicines: English Edition, 2007, 5(1): 45-49.
[0032]
[23] Corpetti C, Del Re A, Seguella L, et al. Cannabidiol inhibits SARS-Cov-2spike(S)protein-induced cytotoxicity and inflammation through a PPARγ-dependent TLR4 / NLRP3 / Caspase-1 signaling suppression in Caco-2cell line[J]. Phytotherapy Research, 2021, 35(12): 6893-6903.
[0033]
[24] He J. The In Vitro Pharmacological Evaluation of Tetrahydrocannabivarin(THCV) for Intestinal Inflammatory Conditions[D]. University of Saskatchewan, 2022. Summary of the invention
[0034] The technical problem to be solved by the present invention is to provide O-carboxymethyl chitosan-g-cholesterol succinate monoester and a preparation method and application thereof in view of the deficiencies in the prior art.
[0035] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0036] The invention discloses a method for preparing O-carboxymethyl chitosan-g-cholesterol succinate monoester, comprising the following steps:
[0037] (1) Cholesterol, 4-dimethylaminopyridine and succinic anhydride are dissolved in dichloromethane and subjected to esterification reaction under the protection of inert gas to obtain cholesterol succinate monoester, denoted as CHS;
[0038] (2) dissolving O-carboxymethyl chitosan in water to obtain a first mixed solution; dissolving CHS obtained in step (1) in N,N-dimethylformamide to obtain a second mixed solution; adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to the second mixed solution for activation reaction to obtain an activation solution; adding the activation solution to the first mixed solution for coupling reaction; after the reaction is completed, centrifuging the reaction solution, dialyzing the supernatant, and freeze-drying the obtained dialyzate to obtain O-carboxymethyl chitosan-g-cholesterol succinate, denoted as CCMC.
[0039] In some embodiments, in step (1), the molar ratio of cholesterol to 4-dimethylaminopyridine and succinic anhydride is 1:1:2; the esterification reaction is carried out at room temperature for 16 to 32 hours, preferably 24 hours; and the inert gas is nitrogen.
[0040] The amount of the solvent dichloromethane used in the esterification reaction is such that the raw materials in the reaction system are dissolved and the viscosity is moderate.
[0041] In some embodiments, in step (2), the concentration of O-carboxymethyl chitosan in the first mixed solution is 5 to 20 mg·mL -1 ; The concentration of CHS in the second mixed solution is 10-12 mg·mL -1; The mass ratio of O-carboxymethyl chitosan to CHS is 1-2:1; the molar ratio of CHS to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:1.5:1.5; the activation reaction has a reaction temperature of room temperature and an activation time of 60 to 100 minutes; the coupling reaction has a reaction temperature of 60 to 90°C and a reaction time of 36 to 54 hours.
[0042] In some embodiments, preferably, in step (2), the concentration of O-carboxymethyl chitosan in the first mixed solution is 10 mg·mL -1 ; The concentration of CHS in the second mixed solution is 11.33 mg·mL -1 ; The mass ratio of O-carboxymethyl chitosan to CHS is 1.5:1; the molar ratio of CHS to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:1.5:1.5; the activation reaction has a reaction temperature of room temperature and an activation time of 80 minutes; the coupling reaction has a reaction temperature of 80°C and a reaction time of 48 hours.
[0043] In some embodiments, in step (2), the reaction solution is centrifuged at 5000 rpm for 20 min; the specific steps of dialysis of the supernatant are: dialyzing the supernatant with water for 48 hours, changing the water every 2 hours, and having a molecular weight cutoff of 8000 to 10000 to remove water-soluble by-products.
[0044] The O-carboxymethyl chitosan-g-cholesterol succinate prepared by the above-mentioned preparation method is also within the protection scope of the present invention.
[0045] The use of the above-mentioned O-carboxymethyl chitosan-g-cholesterol succinate monoester in the preparation of cannabidiol-loaded drug-loaded nanomicelles is also within the protection scope of the present invention.
[0046] Specifically, the use of O-carboxymethyl chitosan-g-cholesterol succinate monoester in the preparation of cannabidiol-loaded drug-loaded nano micelles comprises the following steps:
[0047] (i) mixing the O-carboxymethyl chitosan-g-cholesterol succinate monoester according to claim 4 with water to obtain an amphiphilic polymer mixed solution; stirring the amphiphilic polymer mixed solution at room temperature for 8 to 24 hours, and then subjecting the mixed solution to ultrasonic treatment with a probe under ice bath conditions; after the ultrasonic treatment, centrifuging, filtering, and freeze-drying the mixed solution to obtain amphiphilic polymer blank micelles;
[0048] (ii) dissolving cannabidiol in tetrahydrofuran to obtain a cannabidiol solution; dissolving the amphiphilic polymer blank micelles obtained in step (i) in deionized water to obtain an amphiphilic polymer blank micelle aqueous solution; adding the cannabidiol solution to the amphiphilic polymer blank micelle aqueous solution, stirring at 300-400 rpm for 8-10 hours at room temperature, and after the stirring is completed, placing the reaction solution in a dialysis bag for dialysis, filtering the obtained dialyzate, and freeze-drying to obtain drug-loaded nanomicelles loaded with cannabidiol.
[0049] Wherein, preferably, in step (ii), the cannabidiol solution is added to the aqueous solution of blank micelles of the amphiphilic polymer and stirred at 400 rpm for 10 h at room temperature.
[0050] Specifically, in step (i), the concentration of O-carboxymethyl chitosan-g-cholesterol succinate in the amphiphilic polymer mixture is 0.025-0.5 mg·mL -1 ; The probe is ultrasonically treated, the ultrasonic power is 250 to 400 W, and the ultrasonic time is 5 to 9 minutes.
[0051] Specifically, preferably, in step (i), the concentration of O-carboxymethyl chitosan-g-cholesterol succinate in the amphiphilic polymer mixture is 0.025 mg·mL -1 ; The probe was ultrasonically treated with an ultrasonic power of 350 W and an ultrasonic time of 7 min.
[0052] The centrifugation and filtration of the mixed solution is to centrifuge the mixed solution and then filter it through a 0.45 μm water system microporous filter membrane.
[0053] Specifically, preferably, in step (i), the amphiphilic polymer blank micelles have an average particle size of 173.9±2.3 nm and a Zeta potential of -17.6±1.3 mV.
[0054] Specifically, in step (ii), the concentration of cannabidiol in the cannabidiol solution is 3 to 4 mg·mL -1 ; The concentration of the amphiphilic polymer blank micelles in the amphiphilic polymer blank micelle aqueous solution is 3 to 5 mg·mL -1 ; The volume ratio of tetrahydrofuran in the cannabidiol solution to deionized water in the amphiphilic polymer blank micelle aqueous solution is 1:5-7.
[0055] Specifically, preferably, in step (ii), the concentration of cannabidiol in the cannabidiol solution is 3.33 mg·mL -1 ; The concentration of the amphiphilic polymer blank micelles in the amphiphilic polymer blank micelle aqueous solution is 4 mg·mL -1; The volume ratio of tetrahydrofuran in the cannabidiol solution to deionized water in the amphiphilic polymer blank micelle aqueous solution is 1:6.
[0056] Specifically, preferably, in step (ii), the drug-loaded nanomicelles loaded with cannabidiol have an average particle size of 230.6±1.8 nm, a PDI of 0.170±0.053, and a Zeta potential of -13.5±1.2 mV.
[0057] Specifically, preferably, in step (ii), in the cannabidiol-loaded nanomicelles, the encapsulation efficiency of cannabidiol is 86.35%±0.56%, and the drug loading amount is 9.18%±0.32%.
[0058] In some embodiments, in step (ii), the reaction solution is placed in a dialysis bag for dialyzation, and the specific steps are: placing the reaction solution in a dialysis bag, dialyzing with deionized water for 24 hours, changing the water every 2 hours, with a molecular weight cutoff of 8000 to 10000, and filtering the obtained dialysate through a 0.45 μm organic filter membrane.
[0059] Beneficial effects:
[0060] (1) The present invention successfully prepares the amphiphilic polymer CCMC by reacting cholesterol with succinic anhydride to form an ester via 4-dimethylaminopyridine catalyst, and then the exposed single carboxyl group reacts with the side chain amino group of O-carboxymethyl chitosan under the synergistic catalysis of EDC·HCl and NHS to form an amide bond. The ultrasound-assisted self-assembly technology is combined with the response surface method to optimize the optimal preparation process of blank nanomicelles with the particle size as an index, and then the CBD / CCMC drug-loaded nanomicelles are prepared by dialysis. The results of dynamic light scattering and scanning electron microscopy both confirm that the obtained blank nanomicelles and drug-loaded nanomicelles have appropriate particle sizes and concentrated distribution, stable structures, and spherical shapes.
[0061] (2) The CBD / CCMC drug-loaded nanomicelles prepared by the present invention significantly improve the solubility of CBD in water. In vitro and in vivo experiments have shown that the preparation of CBD / CCMC improves the bioavailability of CBD and improves its intestinal transport efficiency and anti-inflammatory effect.
[0062] (3) The present invention found that the uptake and transport modes of CBD / CCMC drug-loaded nanomicelles in Caco-2 cells include caveolin-dependent and clathrin-dependent endocytosis, passive diffusion, and efflux protein-mediated active transport. CBD transport is affected by efflux proteins BCRP and MRP2, while CBD / CCMC transport is not affected by efflux proteins BCRP and MRP2, but only by efflux protein P-gp. In addition, CBD / CCMC can significantly improve LPS-induced Caco-2 cell inflammatory injury response by inhibiting IL-8, IL-1β, and TNF-α cell inflammatory factors, and can regulate cell viability and TEER values to protect the intestinal mucosal barrier. The present invention provides a strong theoretical basis for the great development of CBD in the field of medicine.
[0063] (4) The present invention found that the uptake and transport modes of CBD and CBD / CCMC in Caco-2 cells include caveolin-dependent and clathrin-dependent endocytosis, passive diffusion, and efflux protein-mediated active transport. In addition, CBD / CCMC can significantly improve the inflammatory injury response and protect the intestinal mucosal barrier by inhibiting cellular inflammatory factors. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.
[0065] Figure 1 This is the synthesis route of O-carboxymethyl chitosan-g-cholesterol succinate (CCMC) in Example 1.
[0066] Figure 2 Infrared spectra of CHOL, CHS, OCMC and CCMC.
[0067] Figure 3A This is the NMR spectrum of CHOL and CHS.
[0068] Figure 3B These are the NMR spectra of OCMC and CCMC.
[0069] Figure 4 The fluorescence emission spectra of pyrene in CCMC nanomicelle solutions with different mass concentrations and I 375 / I 385 and the logarithmic relationship between the mass concentration of CCMC nanomicelles.
[0070] Figure 5 This is the effect of OCMC concentration in the first mixed solution on the particle size and PDI of blank nanomicelles.
[0071] Figure 6This is the effect of the mass ratio of OCMC and CHS on the particle size and PDI of blank nanomicelles.
[0072] Figure 7 This is the effect of activation time on the particle size and PDI of blank nanomicelles.
[0073] Figure 8 This is the effect of ultrasonic power on the particle size and PDI of blank nanomicelles.
[0074] Fig. 9 This is the effect of ultrasound time on the particle size and PDI of blank nanomicelles.
[0075] Fig.10 This is the multiple regression Pareto chart.
[0076] Fig.11 This is the particle size distribution diagram of CCMC blank nanomicelles.
[0077] Fig.12 This is the potential diagram of CCMC blank nanomicelles.
[0078] Fig.13 This is a scanning electron microscope photo of CCMC blank nanomicelles.
[0079] Fig.14 This is the particle size distribution diagram of CBD / CCMC nanomicelles.
[0080] Fig.15 This is the potential diagram of CBD / CCMC nanomicelles.
[0081] Fig.16 This is a scanning electron microscope photo of CBD / CCMC drug-loaded nanomicelles.
[0082] Fig.17 The stability of CBD / CCMC drug-loaded nanomicelles at room temperature and 37°C.
[0083] Fig.18 This is the in vitro release curve of CBD / CCMC drug-loaded nanomicelles.
[0084] Fig.19 This is a standard curve chart of cannabidiol.
[0085] Fig. 20 This is the effect of CCMC blank nanomicelles, CBD and CBD / CCMC drug-loaded nanomicelles on cell survival rate.
[0086] Fig.21 This is the effect of CCMC blank nanomicelles, CBD and CBD / CCMC drug-loaded nanomicelles on cell membrane integrity.
[0087] Fig. 22The status of Caco-2 cells at different growth stages in Transwell chamber.
[0088] Fig.23 To determine the transmembrane electrical resistance (TEER) of Caco-2 cells.
[0089] Fig.24 This is a graph showing the activity of ALP in Caco-2 cell monolayer.
[0090] Fig.25 This is a diagram showing the leakage of the marker (sodium fluorescein).
[0091] Fig.26 The effects of time, concentration, temperature and endocytosis inhibitors on the uptake characteristics of Caco-2 cells.
[0092] Fig. 27 The results of in vivo pharmacokinetic experiments of CBD and CBD / CCMC; A is the blood drug concentration-time curve, and Figure B is the pharmacokinetic parameters.
[0093] Fig.28 The inflammatory response of Caco-2 cells stimulated by different concentrations of LPS; A is the cell survival rate, B is the LDH activity, and C is the level of cellular inflammatory factors.
[0094] Fig.29 The effects of CBD and CBD / CCMC on LPS-induced inflammatory response of Caco-2 cells; A is cell survival rate, B is LDH activity; *P<0.05, ***P<0.001.
[0095] Fig.30 This is the effect of CBD and CBD / CCMC on the TEER of LPS-induced inflammatory response in Caco-2 cells.
[0096] Fig.31 The effects of CBD and CBD / CCMC on the secretion levels of cellular inflammatory factors; A is IL-8, B is IL-1β, and C is TNF-α; ****P<0.0001. DETAILED DESCRIPTION
[0097] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.
[0098] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0099] 1. Experimental Materials
[0100] Cholesterol (analytical grade, batch number: C14217584, Shanghai McLean Biochemical Technology Co., Ltd.); succinic anhydride (analytical grade, batch number: C11891059, Shanghai McLean Biochemical Technology Co., Ltd.); O-carboxymethyl chitosan (MW = 50000, deacetylation degree 90%, substitution degree 85%, batch number: 210902, Qingdao Honghai Biotechnology Co., Ltd.); 4-dimethylaminopyridine (analytical grade, batch number: C13624244, Shanghai McLean Biochemical Technology Co., Ltd.); 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride (batch number: C14749304, Shanghai McLean Biochemical Technology Co., Ltd.); N-hydroxysulfosuccinimide (batch number: C12913793, Shanghai McLean Biochemical Technology Co., Ltd.); dialysis bag (MWCO 8000~14000Da, batch number: 409C021, Jinkelong (Beijing) Biotechnology Co., Ltd.); potassium bromide (spectrally pure, batch number: C14089606, Shanghai McLean Biochemical Technology Co., Ltd.); pyrene (97%, C12790936, Shanghai McLean Biochemical Technology Co., Ltd.); cannabidiol (batch number: 7003, Shanghai Standard Standard Technology Service Co., Ltd.).
[0101] 2. Determination of CBD loading and encapsulation efficiency in CBD / CCMC loaded nanomicelles
[0102] Accurately weigh an appropriate amount of CBD / CCMC drug-loaded nanomicelles and dissolve it in 1 mL of ultrapure water. Add 9 mL of acetonitrile and mix thoroughly before ultrasonication for 30 min to depolymerize the drug-loaded nanomicelles and completely dissolve CBD. Filter through a 0.22 μm microporous filter membrane and inject the sample according to the chromatographic conditions. Record the peak area and calculate the CBD concentration according to the standard curve equation. Calculate the encapsulation efficiency and drug loading according to the following formula.
[0103]
[0104]
[0105] The chromatographic conditions were as follows: chromatographic column: Agilent Eclipse XDB-C18 (250 mm×4.6 mm, 5 μm); mobile phase: acetonitrile: 0.1% phosphoric acid = 80:20; detection wavelength: 210 nm, column temperature: 30.0° C., flow rate: 1.0 mL·min -1 , injection volume: 20μL, detection time: 20min, isocratic elution.
[0106] The CBD standard curve was established by accurately weighing 25.00 mg of CBD reference substance into a 25 mL volumetric flask, adding acetonitrile to the scale line, and shaking well to obtain 1 g·L -1Mother solution. Transfer appropriate amount of mother solution to 10mL volumetric flask, dilute to scale with acetonitrile, and prepare 2, 5, 10, 20, 40, 60, 80, 100, 150μg·mL -1 The acetonitrile solution of CBD was filtered through a 0.22 μm organic microporous filter membrane and tested according to the chromatographic conditions. The linear regression equation of CBD was obtained by taking the different concentrations of the drug as the horizontal axis and the chromatographic peak area as the vertical axis. The CBD standard curve is shown in the figure below. Fig.19 As shown, the results showed that CBD was in the range of 2 to 200 μg mL -1 The linear relationship is good within the concentration range, and the CBD linear regression equation is: Y = 145610X-47161, R 2 =0.9999.
[0107] Example 1: Preparation of O-carboxymethyl chitosan-g-cholesterol succinate (CCMC)
[0108] (1) Synthesis of Cholesteryl Succinate (CHS):
[0109] Accurately weigh cholesterol (3.8665 g, 10 mmol), 4-dimethylaminopyridine (1.2217 g, 10 mmol) and succinic anhydride (2.0014 g, 20 mmol) and dissolve in 25 mL of anhydrous dichloromethane. Stir under nitrogen at room temperature for esterification for 24 h. After the reaction, add 25 mL of DCM to the reaction system, wash twice with 1 wt% hydrochloric acid, separate the liquids, collect the lower organic phase, add 5 g of anhydrous sodium sulfate solid to the organic phase, stir for 30 min to remove moisture, filter, and concentrate the filtrate. The product is placed in a vacuum drying oven and dried at 50°C to obtain cholesterol succinate, recorded as CHS.
[0110] (2) Synthesis of CCMC:
[0111] O-carboxymethyl chitosan (OCMC, 0.5 g) was completely dissolved in 50 mL of distilled water to obtain a first mixed solution; CHS (0.34 g) obtained in step (1) was dissolved in 30 mL of DMF to obtain a second mixed solution; EDC·HCl and NHS (the molar ratio of the two to CHS was 1.5:1) were then added to the second mixed solution, and the mixture was stirred at room temperature for 60 min to perform an activation reaction to obtain an activation solution; the activation solution was uniformly added to the first mixed solution and the coupling reaction was performed at 80° C. for 48 h; after the reaction was completed, the reaction solution was centrifuged at 5000 rpm for 20 min, and the supernatant was dialyzed with distilled water for 48 h, with a molecular weight cutoff of 8000-10000, and the water was changed every 2 h to remove water-soluble byproducts, and the dialyzate was freeze-dried to obtain O-carboxymethyl chitosan-g-cholesterol succinate powder, which was recorded as CCMC.
[0112] The synthetic route of O-carboxymethyl chitosan-g-cholesteryl succinate (CCMC) is shown in Figure 1 First, cholesterol and succinic anhydride are catalyzed by 4-dimethylaminopyridine to form esters, and the exposed single carboxyl group reacts with the side chain amino group of O-carboxymethyl chitosan under the synergistic catalysis of EDC·HCl and NHS to form an amide, which is the amphiphilic polymer CCMC.
[0113] Example 2: Validation of O-carboxymethyl chitosan-g-cholesterol succinate
[0114] (1) Fourier transform infrared (FT-IR) spectroscopy characterization: 2 mg of each of cholesterol (CHOL), CHS (prepared in Example 1), OCMC, and CCMC (prepared in Example 1) were finely ground with 200 mg of spectral grade potassium bromide powder in an agate mortar, mixed and pressed into tablets, and detected by infrared spectroscopy with a NICOLET IS10 Fourier spectrometer. The specific infrared spectrum is shown in Figure 2 As can be seen from the figure, comparing the infrared spectra of cholesterol and CHS, 3404cm -1 The disappearance of the stretching vibration peak of the alcohol hydroxyl group and the appearance of the characteristic peak of the carboxyl group indicate that the succinyl group is connected to the OH group at position 3 of cholesterol by an ester bond. In the infrared spectrum of OCMC, the wave number is 1602 cm -1 The characteristic absorption band at 1650cm is the amide II band, which corresponds to the bending vibration of NH on the primary amino group; -1 The position is the amide I band, corresponding to the C=O stretching vibration absorption peak; but due to the 1602cm -1 The absorption peak at 1602 cm-1 is larger, which makes the absorption peaks of amide I and amide II unclear, indicating that the degree of deacetylation of OCMC is higher and there are more active amino groups. Compared with OCMC, the infrared spectrum of CCMC shows two distinct absorption peaks, located at 1602 cm-1. -1 The absorption peak intensity of the amide II band was significantly reduced, and the peak at 1650 cm -1 The absorption peak of the amide I band showed a relatively enhanced trend. This result revealed that skeleton coupling occurred between CHS and OCMC, forming more amide bonds, confirming the successful synthesis of CCMC.
[0115] (2) H NMR spectroscopy ( 1 H-NMR) characterization: 5 mg of cholesterol and CHS (prepared in Example 1) were weighed and dissolved in CDC1 3 (TMS internal standard); 5 mg OCMC and CCMC (prepared in Example 1) were weighed and dissolved in 0.5 mL D 2 O solution, transfer the sample to a nuclear magnetic resonance tube, and detect it in a nuclear magnetic resonance instrument (working frequency 600MHz). The specific nuclear magnetic resonance spectrum is shown in Figure 3A , Figure 3B From the figure, we can see that the chemical shift of H at position 3 in cholesterol is from 3.52ppm (1H,m,3-H 1 ) became 4.63ppm (1H, m, 3-H 1 ), shifted 1.1 ppm downfield, plus 2.59 ppm in the CHS product (2H, m, succinyl-COCH 2 ), 2.67 ppm (2H, m, succinyl-CH 2 CO) indicates that succinyl reacts with the hydroxyl group at position 3 of cholesterol to form an ester. For OCMC, a broad absorption peak of the sugar ring skeleton proton appears in the range of 3.36-4.17 ppm, and the characteristic peak at 2.02 ppm is attributed to the methyl hydrogen on N-acetylglucosamine (-COCH 3 ); In the NMR spectrum of the product CCMC, the broad peak in the range of 3.36-4.17 ppm corresponds to the proton absorption peak in the sugar ring skeleton, but the absorption peak at 2.02 ppm is significantly enhanced compared with OCMC. The reason is that the methyl hydrogen (-COCH 3 ) and the large amount of -CH 2 The peaks are superimposed, and the absorption of some small peaks in the range of 1.0 to 3.0 ppm is enhanced, proving that the CCMC product is successfully synthesized.
[0116] Example 3: Optimization of the preparation process of CCMC blank nanomicelles
[0117] (1) The O-carboxymethyl chitosan-g-cholesterol succinate CCMC used in this example was prepared according to the preparation method of Example 1, except that the concentration of OCMC in the first mixed solution during the preparation of the CCMC amphiphilic polymer was changed (5, 10, 15, 20, 25 mg mL -1 ), OCMC to CHS mass ratio (2:1, 1.5:1, 1:1, 1:1.5, 1:2), activation time (40, 60, 80, 100, 120 min), and finally the polymer CCMC prepared under different conditions was obtained. Subsequently, the obtained CCMC in different batches was used to prepare amphiphilic polymer blank micelles.
[0118] (2) Determination of critical micelle concentration of amphiphilic polymers: The CCMC nanomicelles were determined by steady-state fluorescence spectroscopy, with pyrene as the fluorescent probe, and 6×10 -5100 μL of pyrene acetone solution was placed in a 15 mL stoppered test tube, and the acetone was blown dry with nitrogen. A series of solutions with mass concentrations of 0.0001, 0.001, 0.005, 0.01, 0.05, 0.1, 0.5, and 1 mg mL were prepared. -1 The CCMC nanomicelle aqueous solution (the final concentration of pyrene in the solution was 6×10 -7 mol·L -1 ), vortexed for 1 min, sonicated for 40 min, and allowed to stand overnight at room temperature in the dark. The fluorescence emission spectrum of pyrene in the solution was determined using a fluorescence spectrophotometer. The excitation wavelength was 334 nm, the excitation bandwidth and emission bandwidth were 10 nm and 5 nm, respectively, and the fluorescence emission spectrum scanning range was 360-480 nm. The fluorescence intensity I of pyrene was 375 / I 385 Plot the logarithm of the concentration and calculate the critical micelle concentration.
[0119] like Figure 4 As shown in A, the fluorescence intensity of pyrene increases with the increase of the mass concentration of CCMC nanomicelle solution. Figure 4 B shows the fluorescence intensity ratio of the first emission peak at 375 nm and the third emission peak at 385 nm of pyrene in CCMC nanomicelle solution. 375 / I 385 The relationship between the logarithm of the mass concentration of CCMC nanomicelle solution. The CCMC corresponding to the intersection of the two tangents in this figure is 0.025 mg·mL -1 This indicates that CCMC at lower concentrations can self-assemble in aqueous solution with good stability.
[0120] (3) Preparation of amphiphilic polymer blank micelles by ultrasonic probe-assisted self-assembly and single factor investigation:
[0121] Preparation of amphiphilic polymer blank micelles: O-carboxymethyl chitosan-g-cholesterol succinate (CCMC prepared in different batches in Example (1)) was mixed with water to obtain an amphiphilic polymer mixed solution (the concentration of CCMC in the mixed solution was 0.025 mg mL -1 ); after stirring the amphiphilic polymer mixture at room temperature for 12 hours, the mixture was subjected to probe ultrasonic treatment under ice bath conditions (to avoid excessive solution temperature, the pulse was on for 5 seconds and off for 5 seconds); after the ultrasonic treatment, the mixture was centrifuged at 5000 rpm for 20 minutes, and the supernatant was filtered through a 0.45 μm water-based microporous filter membrane and freeze-dried to obtain a CCMC blank nanomicelle solid sample.
[0122] Among them, a single factor study was conducted: the concentration of OCMC in the first mixed solution (5, 10, 15, 20, 25 mg mL -1), mass ratio of OCMC to CHS (2:1, 1.5:1, 1:1, 1:1.5, 1:2), activation time (40, 60, 80, 100, 120 min); in the preparation process of CCMC blank nanomicelles, probe ultrasound was performed with ultrasonic powers (200, 250, 300, 350, 400 W) and ultrasonic time (3, 5, 7, 9, 11 min) under ice bath conditions to obtain batches of CCMC blank nanomicelle samples, and the surface Zeta potential, particle size and polydispersity index (PDI) of the blank nanomicelles were determined using Zetasizer Nano ZS90.
[0123] (4) Single factor experimental results:
[0124] Effect of OCMC concentration in the first mixed solution on the particle size and PDI of blank nanomicelles:
[0125] like Figure 5 As shown in the figure, with the increase of OCMC concentration in the first mixed solution, the particle size and PDI of the blank nanomicelles first decreased and then increased. This is because as the OCMC concentration increases, the reaction is promoted in the forward direction; when the OCMC concentration is too high, the viscosity of its aqueous solution increases significantly, hindering the reaction. Therefore, the OCMC concentration of 10 mg mL -1 is the optimal concentration, at which time the particle size and PDI of the blank nanomicelles reach the minimum values, which are 196.16±1.5nm and 0.165±0.006, respectively.
[0126] Effect of OCMC and CHS mass ratio on the particle size and PDI of blank nanomicelles: Figure 6 As shown in the figure, as the proportion of CHS increases, the particle size and PDI of the blank nanomicelles first decrease and then increase. This may be because the increase in the proportion of CHS can provide more active carboxyl groups for grafting with the side chain amino groups of OCMC. When the proportion of CHS is too high, the viscosity coefficient of the solution may increase due to the increase in hydrophobic substances and cross-linking agents EDC·HCl and NHS, which hinders the reaction. Therefore, the mass ratio of OCMC and CHS of 1.5:1 is selected as the optimal ratio. At this time, the particle size and PDI value of the blank nanomicelles are the smallest, which are 190.7±2.1nm and 0.169±0.005, respectively.
[0127] Effect of activation time on the particle size and PDI of blank nanomicelles: Figure 7As shown in the figure, when the activation time is less than 80min, the particle size of CCMC blank nanomicelles gradually decreases with the increase of activation time. This may be because more carboxyl groups in CHS molecules are activated and grafted to the side chain amino groups of OCMC. Under the action of the ultrasonic probe, the hydrophobic internal driving force causes the particle size of CCMC blank nanomicelles to become smaller and the distribution is concentrated. When the activation time exceeds 80min, the activation intermediate may be inactivated and the amide bond formation is reduced, resulting in the increase of the particle size of CCMC blank nanomicelles. Therefore, the optimal activation time is selected as 80min, at which time the particle size is 188.2±2.3nm and the PDI value is 0.180±0.013.
[0128] Effect of ultrasonic power on the particle size and PDI of blank nanomicelles: Figure 8 As shown in the figure, from the overall numerical distribution, the effect of ultrasonic power on particle size and PDI is very significant. When the ultrasonic power is lower than 350W, the particle size and PDI value gradually decrease with the increase of ultrasonic power, and the ultrasonic power enhances the self-assembly driving force; when the ultrasonic power is greater than 350W, the stable micelle structure will be destroyed due to the excessive ultrasonic power. Therefore, the ultrasonic power of 350W was finally selected.
[0129] Effect of ultrasonic time on the particle size and PDI of blank nanomicelles: Fig. 9 As shown in the figure, from the overall numerical distribution, the effect of ultrasound time on particle size and PDI is relatively low. The longer the ultrasound time, the more complete the self-assembly effect induced by ultrasound, and the smaller the particle size value. The particle size is close to saturation at around 7 minutes. If the ultrasound time is further extended, the structure of CCMC blank nanomicelles is partially destroyed, resulting in an increase in particle size. After comprehensive consideration, the ultrasound time is selected as 7 minutes. Under this condition, the particle size and PDI reach the optimal values, which are 182.1nm and 0.160±0.008, respectively.
[0130] (5) Plackett-Burman experiment and results
[0131] According to the results of the single factor experiment, the effects of OCMC concentration, OCMC to CHS mass ratio, activation time, ultrasonic power and ultrasonic time on the particle size of CCMC blank nanomicelles were investigated. The Plackett-Burman experiment was used to screen out the significant factors affecting the particle size and PDI of CCMC blank nanomicelles. Each factor was taken at two levels, high (+1) and low (-1), and 12 groups of experiments were conducted. The experimental factors and level values are shown in Table 1.
[0132] Table 1. Factors and levels of the Plackett-Burman experiment
[0133]
[0134]
[0135] The results of the Plackett-Burman experiment and the effect evaluation of each factor are shown in Table 2 and Table 3. As shown in Table 3, the significant factors affecting the particle size and PDI of CCMC blank micelles are the mass ratio of OCMC to CHS, activation time and ultrasonic power, while OCMC concentration and ultrasonic time are relatively non-significant factors. Therefore, the three key factors of activation time, ultrasonic power, and mass ratio of OCMC to CHS were selected for further response surface optimization design and analysis. In subsequent experiments, the OCMC concentration and ultrasonic time were fixed at 10 mg·mL -1 and 7min.
[0136] Table 2 Plackett-Burman experimental design and results
[0137]
[0138] Table 3 Evaluation of the effects of various factors in the Plackett-Burman experiment
[0139]
[0140] Note: * indicates significant difference (P<0.05), ** indicates extremely significant difference (P<0.01).
[0141] Minitab 2018 software was used to perform multiple regression analysis on the data in Table 2, and the fitting equation was obtained: Z 1 =232.26+3.71C 1 -8.67C 2 -16.04C 3 -12.11C 4 +3.07C 5 At the same time, we get the multivariate regression Pareto arrangement diagram. Fig.10 As shown in the figure, the three factors of ultrasonic power, activation time and mass ratio of OCMC to CHS have significant effects on the particle size and PDI of the prepared CCMC blank nanomicelles, and the order of influence is: activation time (C 3 )>Ultrasonic power(C 4 )>OCMC and CHS mass ratio (C 2 ). Therefore, these three factors were selected as significant factors to conduct the steepest climbing experiment and Box-Behnken experiment.
[0142] (6) Steepest climbing test and results
[0143] Through the steepest climbing experiment, the values of important factors are brought close to the optimal region, and an effective response surface fitting equation is established. According to the first-order fitting equation obtained from the Plackett-Burman experiment, the climbing direction and step length of each important factor are designed to determine the optimal value of each factor.
[0144] The climbing direction is determined by the variable relationship of three important factors in the Plackett-Burman experimental regression equation. Among them, the mass ratio of OCMC to CHS (C 2 ), activation time (C 3 ), ultrasonic power (C 4 ) are all negative effects. Table 4 shows the design and results of the steepest climbing experiment. The results show that the best particle size condition is experiment No. 3, so the conditions in experiment No. 3 are used as the center point of the subsequent Box-Behnken experiment.
[0145] Table 4 Steepest climbing experiment design and results
[0146]
[0147] (7) Response surface optimization experiment - Response surface optimization of CCMC blank nanomicelle preparation process
[0148] Based on the results of Plackett-Burman experiment and steepest climbing test, the mass ratio of OCMC to CHS (C 2 ), activation time (C 3 ) and ultrasonic power (C 4 )3 significant factors as response factors, and the nanomicelle size as response value (Z) to conduct a three-factor three-level Box-Behnken experiment. The experimental factors and levels are shown in Table 5.
[0149] Table 5 Factors and levels of Box-Behnken design
[0150]
[0151] Regression model establishment and variance analysis:
[0152] Based on the results of Plackett-Burman experiment and steepest climbing test, other experimental conditions remain unchanged and the mass ratio of OCMC to CHS (C 2 ), activation time (C 3 ) and ultrasonic power (C 4 ) is the response factor, and the blank nanomicelle particle size (Z) is the response value. Design-Expert 13.0.1.0 software was used to design 17 experiments with three factors and three levels (Table 6). The fitting equation obtained by regression analysis of the experimental data was: Z = 173.68 + 1.45C2 -1.97C 3 -1.85C 4 -2.95C 2 C 3 -0.5C 2 C 4 +0.85C 3 C 4 +14.69C 2 2 +30.89C 3 2 +27.28C 4 2 .
[0153] As shown in Table 7, the model F value is 334.15, P < 0.0001, and the model is extremely significant. The model lack of fit term P = 0.2225 (P > 0.05), the lack of fit term is not significant, indicating that the model has a good fit. The coefficient of variation CV is 0.8327%, indicating that the experimental results have high precision, the data is reasonable and reliable, and can be used to predict the particle size of CCMC blank nanomicelles. The first-order term C 3 , C 4 , the interaction term C 2 C 3 and the quadratic term C 2 2 , C 3 2 , C 4 2 The influence on the particle size of blank nanomicelles was significant (P<0.01). According to the F value, among the three single factors that significantly affected the particle size of CCMC blank nanomicelles, the influence degree was ranked from large to small as follows: C 3 (Activation time)>C 4 (ultrasonic power)>C 2 (OCMC to CHS mass ratio), which is consistent with the Plackett-Burman experimental results.
[0154] Table 6 Response surface optimization experimental design and experimental results
[0155]
[0156] Table 7 Response surface variance analysis table
[0157]
[0158]
[0159] Note: * indicates significant difference (P<0.05), ** indicates extremely significant difference (P<0.01).
[0160] Optimization process verification experiment:
[0161] The experimental results were processed by Design-Expert 13.0.1.0 software to predict the optimal preparation process conditions: the fixed OCMC concentration and ultrasonic time were 10 mg·mL -1 and 7min, OCMC to CHS mass ratio of 1.477:1, activation time of 80.59min, ultrasonic power of 351.63W, the optimal particle size of CCMC blank nanomicelles predicted under this process is 173.6nm. Based on the feasibility of the actual operation of the experiment, the above predicted process parameters were adjusted as follows: OCMC to CHS mass ratio of 1.5:1, activation time of 80min, ultrasonic power of 350W. In order to verify the optimized process conditions, three parallel experiments were carried out, and the average particle size of CCMC blank nanomicelles was measured to be 173.9±2.3nm, which is close to the predicted value of 173.6nm, indicating that the model is accurate and the process conditions are highly practical.
[0162] (8) Particle size distribution and Zeta potential determination of blank nanomicelles
[0163] An appropriate amount of CCMC blank nanomicelle sample (the preparation method refers to the "Preparation of amphiphilic polymer blank micelles" under "(3)" in Example 3, the CCMC preparation method used refers to Example 1, and the process parameters are the optimal process parameters obtained by the "Optimized process verification experiment" under "(7)" in Example 3)) was dissolved in deionized water, and the surface Zeta potential, particle size and polydispersity index PDI of CCMC blank nanomicelles were measured using Zetasizer Nano ZS90. An appropriate particle size is conducive to the effective loading of CBD; the larger the absolute value of the Zeta potential, the stronger the stability of the nanomicelles. Fig.11 , Fig.12 The average particle size of the best CCMC blank nanomicelles was measured to be 173.9±2.3nm, and the potential was -17.6±1.3mV, indicating that the prepared CCMC blank nanomicelles have suitable performance and can efficiently load CBD.
[0164] (9) Scanning electron microscopy (SEM) surface morphology observation of blank nanomicelles
[0165] Take an appropriate amount of CCMC blank nano-micelle freeze-dried powder (prepared under the above optimal process parameters) and stick it on the conductive carbon film double-sided adhesive, put it on the sample stage of the ion sputtering instrument and spray gold for 30 seconds, observe and take pictures under a scanning electron microscope. Fig.13 As shown, the CCMC blank nanomicelle freeze-dried sample has a spherical structure under scanning electron microscopy, with a smooth surface and uniform distribution, indicating that the sample can self-assemble into a spherical structure under the action of ultrasonic probe treatment.
[0166] Example 4: Preparation, Optimization and Characterization of CBD / CCMC Drug-Loaded Nanomicelles
[0167] (1) Preparation of CBD / CCMC drug-loaded nanomicelles
[0168] The preparation method of CCMC used in this example is the same as that in Example 1, except that the concentration of OCMC in the first mixed solution is 10 mg·mL -1 , the mass ratio of OCMC to CHS is 1.5:1, and the activation time is 80 minutes.
[0169] (i) CCMC (prepared in this example) was mixed with water to obtain an amphiphilic polymer mixed solution (the concentration of CCMC in the mixed solution was 0.025 mg mL -1 ); after stirring the amphiphilic polymer mixture at room temperature for 12 hours, the mixture was subjected to probe ultrasonic treatment under ice bath conditions, with an ultrasonic power of 350 W and an ultrasonic time of 7 minutes (to avoid excessive solution temperature, the pulse was on for 5 seconds and stopped for 5 seconds); after the ultrasonic treatment, the mixture was centrifuged at 5000 rpm for 20 minutes, and the supernatant was filtered through a 0.45 μm water-based microporous filter membrane and freeze-dried to obtain a CCMC blank nanomicelle solid sample.
[0170] (ii) dissolving cannabidiol (CBD) in an organic solvent to obtain a CBD solution; dissolving the CCMC blank nano-micelle powder obtained in step (i) in 10 mL of deionized water, stirring at 25° C. for 30 min to obtain a CCMC blank nano-micelle aqueous solution. The CBD solution was added dropwise to the CCMC blank nano-micelle aqueous solution, and stirred at 25° C. After the reaction was completed, the reaction solution was transferred to a dialysis bag, and dialyzed with deionized water for 24 h, with the water being changed every 2 h, and the molecular weight cut-off was 8000-10000. The dialyzate obtained was filtered through a 0.45 μm organic filter membrane, and after freeze-drying, cannabidiol-loaded nano-micelles, i.e., CBD / CCMC drug-loaded nano-micelles, were obtained.
[0171] (2) Single factor experiment of preparation process
[0172] The preparation method in Example 4 (1) was subjected to a single factor experiment, with the selection of organic solvents [CBD / CCMC group: ethanol, DMSO, DMF, acetone, THF], CBD dosage [CBD / CCMC group: 0.5, 1, 1.5, 2, 2.5 mg], CCMC blank nanomicelle concentration in CCMC blank nanomicelle aqueous solution [CBD / CCMC group: 2, 3, 4, 5, 6 mg mL -1], organic phase / aqueous phase volume ratio [CBD / CCMC group: 1:3, 1:4, 1:5, 1:6, 1:7], stirring time [CBD / CCMC group: 4, 6, 8, 10, 12h], stirring speed [CBD / CCMC group: 300, 400, 500, 600, 700rpm / min] were taken as influencing factors to explore their effects on the particle size, PDI, encapsulation efficiency and drug loading of drug-loaded nanomicelles, and to obtain the optimal preparation process; Note: The organic phase / aqueous phase volume ratio here refers to the organic solvent in the CBD solution / deionized water in the CCMC blank nanomicelle aqueous solution; the stirring time and stirring speed here refer to the stirring time and stirring speed after the CBD solution is dropwise added into the CCMC blank micelle aqueous solution.
[0173] (3) Single factor experimental results
[0174] Selection of organic solvent: CBD / CCMC nanomicelles were prepared by dialysis method, while keeping other factors in the prescription unchanged (dosage was 1.5 mg, blank nanomicelle concentration was 4 mg mL -1 , the volume ratio of organic phase to aqueous phase was 1:5, stirring time was 8h and stirring speed was 400rpm), and the organic phase was changed to ethanol, DMSO, DMF, acetone, and THF. The effect of the choice of organic phase on the particle size, PDI, drug loading and encapsulation efficiency of CBD / CCMC drug-loaded nanomicelles was investigated.
[0175] As shown in Table 8, when the organic reagent is ethanol, DMSO, or DMF, the encapsulation efficiency and drug loading are extremely low, and the product particle size is too large, the particle size dispersibility is poor, and the CBD loading effect is not good. When the organic solvent is THF, the encapsulation efficiency and drug loading reach the maximum value, which are 71.32% and 7.49%, respectively. This may be because the cholesterol succinyl structure in CCMC is derived from cholesterol, making CCMC relatively more soluble in THF. CCMC can be effectively dissolved in a mixed system of THF and water, so that CBD and CCMC are in contact to the greatest extent, ensuring the excellent encapsulation efficiency and drug loading of the drug-loaded nanomicelles prepared by the subsequent dialysis method. Therefore, THF was finally selected as the organic solvent.
[0176] Table 8 Effect of organic solvent selection on CBD / CCMC
[0177]
[0178] CBD dosage: As shown in Table 9, when the dosage is in the range of 0.5-2.0 mg, the encapsulation efficiency and drug loading gradually increase, which may be because with the increase of CBD input, the blank nano-micelles have not reached the saturation state of CBD loading; when the dosage is 2 mg, the encapsulation efficiency and drug loading reach the maximum value of 80.95% and 9.07%; but when the dosage is greater than 2 mg, the blank nano-micelles reach the limit of CBD loading, and the encapsulation efficiency and drug loading show a downward trend. Considering comprehensively, the best dosage is selected as 2 mg.
[0179] Table 9 Effect of dosage on CBD / CCMC
[0180]
[0181] Blank nanomicelle concentration in blank nanomicelle aqueous solution: When other conditions are constant, the increase of blank nanomicelle concentration in blank nanomicelle aqueous solution can increase the encapsulation efficiency and drug loading of the prepared drug-loaded nanomicelles to a certain extent. However, when the blank nanomicelle concentration increases to a certain extent, the encapsulation efficiency and drug loading of the drug-loaded nanomicelles basically do not increase much and will cause the loss of blank nanomicelles. As shown in Table 10, as the CCMC blank nanomicelle concentration increases from 2 to 6 mg·mL -1 The encapsulation of the obtained drug-loaded nanomicelles first increased and then stabilized, and the drug loading first increased and then decreased slightly. -1 When the encapsulation efficiency reached 80.96%, the drug loading was also high at 9.11%, so the optimal blank nanomicelle concentration was selected as 4 mg mL -1 .
[0182] Table 10 Effect of blank nanomicelle concentration on CBD / CCMC
[0183]
[0184] Organic phase / aqueous phase volume ratio: As shown in Table 11, when the organic phase / aqueous phase volume ratio is in the range of 1:3 to 1:7, as the proportion of the aqueous phase increases, the encapsulation efficiency and drug loading of the prepared drug-loaded nanomicelles first increase and then decrease. When the organic phase / aqueous phase volume ratio is 1:6, the encapsulation efficiency and drug loading reach the maximum value, which are 83.71% and 9.54%, respectively, and the PDI is 0.170±0.031, and the particle size distribution is concentrated. This condition is conducive to the formation of drug-loaded nanomicelles and the improvement of drug loading capacity. Therefore, the optimal value of the organic phase / aqueous phase volume ratio was finally selected as 1:6.
[0185] Table 11 Effect of organic phase / aqueous phase volume ratio on CBD / CCMC
[0186]
[0187] Stirring time: As shown in Table 12, when the stirring time is 8h, the drug loading and encapsulation efficiency reach the peak value; when the stirring time is less than 8h, the encapsulation efficiency and drug loading continue to increase with the extension of the stirring time; when the stirring time exceeds 8h, the encapsulation efficiency and drug loading gradually decrease. This may be because the initial extension of the stirring time makes the organic phase and the aqueous phase mixed system stable, so that the CBD and CCMC blank nanomicelles are fully in contact, which is conducive to the subsequent dialysis method for CBD loading; when the stirring time is too long, it will reduce the stability index of the CBD / CCMC nanomicelle structure prepared by the dialysis method, resulting in low encapsulation efficiency and drug loading. Therefore, the optimal stirring time is selected as 8h.
[0188] Table 12 Effect of stirring time on CBD / CCMC
[0189]
[0190]
[0191] Stirring speed: As can be seen from Table 13, when the stirring speed is 400rpm, the encapsulation rate and drug loading of the prepared CBD / CCMC nanomicelles reach the maximum, which are 83.90% and 9.57% respectively. When the stirring speed is lower than 400rpm, the encapsulation rate and drug loading of the drug-loaded nanomicelles increase, indicating that the increase in stirring speed is conducive to the uniformity of the dispersion of the organic phase in the aqueous phase, and the performance of the drug-loaded nanomicelles finally prepared is also improved; when the stirring speed exceeds 400rpm, the drug loading and encapsulation rate of the drug-loaded nanomicelles decrease slightly, which may be because the excessive stirring speed destroys the stable structure of the drug-loaded nanomicelles and cannot load more CBD. Therefore, the optimal stirring speed is selected as 400rpm.
[0192] Table 13 Effect of stirring speed on CBD / CCMC
[0193]
[0194] (4) Orthogonal experiment and results
[0195] Based on the results of the single-factor experiment, the CBD / CCMC group selected four factors: dosage, blank nanomicelle concentration, organic phase / aqueous phase volume ratio, and stirring time for L 9 (3 4 ) Orthogonal table design orthogonal experiment, using encapsulation efficiency and drug loading as evaluation indicators to determine the best combination. The factor level table is shown in Table 14.
[0196] Table 14 Orthogonal factor level design table (CBD / CCMC group)
[0197]
[0198] Results of orthogonal experiment of CBD / CCMC group: The results of orthogonal experiment of CCMC group are shown in Table 15. As shown in Table 16 and Table 17, taking encapsulation efficiency and drug loading as the evaluation indexes, according to the R value, the influencing factors are X 3 >X 2 >X 1 >X 4 , that is, the volume ratio of organic phase / aqueous phase>CCMC blank nanomicelle concentration>dosage>stirring time. The optimal process conditions are X 1 2X 2 2X 3 2X 4 3. The optimal preparation process is: the fixed organic reagent is THF, the stirring speed is 400rpm, the organic phase / aqueous phase volume ratio is 1:6, and the blank nanomicelle concentration is 4mg·mL -1 , dosage is 2 mg, stirring time is 10 h.
[0199] Table 15 Orthogonal experiment results (CBD / CCMC group)
[0200]
[0201]
[0202] Table 16 Encapsulation efficiency range analysis (CBD / CCMC group)
[0203]
[0204] Table 17 Drug loading range analysis (CBD / CCMC group)
[0205]
[0206] (5) Verification experiments and results
[0207] According to the above optimal formulation process (prepared according to the optimal preparation process parameters in "(4) Orthogonal experiment and results" in Example 4, and the method of "(1) Preparation of CBD / CCMC drug-loaded nanomicelles" in Example 4), three batches of CBD / CCMC drug-loaded nanomicelles were prepared, their morphology was observed, and their encapsulation efficiency and drug loading were measured respectively. The encapsulation efficiency of the CBD / CCMC group was 86.35%±0.56%, and the drug loading was 9.18%±0.32%.
[0208] (6) Results of water solubility test of cannabidiol
[0209] Weigh an excess of CBD sample and CBD / CCMC drug-loaded nanomicelles (prepared according to the optimal preparation process parameters in "(4) Orthogonal experiment and results" in Example 4, and the method in "(1) Preparation of CBD / CCMC drug-loaded nanomicelles" in Example 4) in a 100 mL conical flask, add 50 mL of deionized water, and stir at 200 rpm for 48 h at 37 ° C. The suspension was centrifuged at 5000 rpm for 20 min, 1 mL of the supernatant was added with 9 mL of acetonitrile, mixed and ultrasonicated for 5 min, filtered through a 0.22 μm organic microporous filter membrane, and the CBD content was determined according to the chromatographic conditions described above.
[0210] The results showed that the water solubility of raw CBD was 0.124 μg mL -1 , while the solubility of CBD in CBD / CCMC loaded nanomicelles was 68.24 μg·mL -1 , that is, the water solubility of CBD in CBD / CCMC drug-loaded nanomicelles increased by 550 times.
[0211] (7) Determination of particle size distribution and zeta potential of CBD / CCMC drug-loaded nanomicelles
[0212] Take an appropriate amount of CBD / CCMC drug-loaded nanomicelle powder and prepare 2.0 mg mL with deionized water. -1 The concentration was measured and the surface Zeta potential, particle size and PDI of the drug-loaded nanomicelles were determined.
[0213] Three batches of CBD / CCMC drug-loaded nanomicelles were prepared using the optimal process obtained by orthogonal optimization (prepared according to the optimal preparation process parameters in "(4) Orthogonal experiment and results" in Example 4, and the method in "(1) Preparation of CBD / CCMC drug-loaded nanomicelles" in Example 4). The average particle size, PDI and Zeta potential were 230.6±1.8 nm, 0.170±0.053 and -13.5±1.2 mV, respectively. The particle size and potential measurement results are shown in Fig.14 , Fig.15 .
[0214] (8) Scanning electron microscopy (SEM) surface morphology observation of drug-loaded nanomicelles
[0215] Take an appropriate amount of CBD / CCMC nanomicelle freeze-dried powder (prepared according to the optimal preparation process parameters in "(4) Orthogonal experiment and results" in Example 4, and the method in "(1) Preparation of CBD / CCMC drug-loaded nanomicelles" in Example 4) and stick it on the conductive carbon film double-sided tape, place it on the sample stage of the ion sputtering instrument, spray gold for 30 seconds, observe and photograph under a scanning electron microscope.
[0216] from Fig.16It can be seen that the CBD / CCMC drug-loaded nanomicelles have regular microscopic morphology, are approximately spherical, and have a smooth surface. The particle size of the CBD / CCMC drug-loaded nanomicelles is significantly larger than that of the blank nanomicelles.
[0217] (9) Stability study of CBD / CCMC drug-loaded nanomicelles
[0218] The CBD / CCMC drug-loaded nanomicelles prepared by the optimal process (prepared according to the optimal preparation process parameters in "(4) Orthogonal experiment and results" in Example 4, and the method in "(1) Preparation of CBD / CCMC drug-loaded nanomicelles" in Example 4) were placed in a vial and placed at room temperature and 37°C. The particle size changes of the two groups of drug-loaded nanomicelles were measured at 24 h, 48 h, 72 h, 120 h and 168 h, respectively, to observe the stability of the drug-loaded nanomicelles.
[0219] Depend on Fig.17 As shown, the particle size of CBD / CCMC drug-loaded nanomicelles did not change significantly at room temperature and 37°C, indicating that during the storage process of up to 7 days, CBD / CCMC drug-loaded nanomicelles showed good storage stability at different temperatures.
[0220] (10) In vitro release study of drug-loaded nanomicelles
[0221] Weigh two portions of CBD / CCMC drug-loaded nanomicelle freeze-dried powder (prepared according to the optimal preparation process parameters in "(4) Orthogonal experiment and results" in Example 4, and the method of "(1) Preparation of CBD / CCMC drug-loaded nanomicelles" in Example 4), dissolve them in 1 mL of deionized water, encapsulate them in dialysis bags (molecular weight cutoff 3500 Da), place them in 20 mL of PBS solution containing 0.5% Tween 80 (w / v) at pH = 5.5 and pH = 7.4, respectively, and place them in a constant temperature shaker at 37°C and an oscillation rate of 100 rpm to simulate in vitro drug release. Take 1 mL of samples at 0.5, 1, 2, 4, 6, 8, 10, 12, 24, 48, 72, 96, 120 and 144 h, respectively, and test them three times in parallel each time, and replace the release medium of each sample with an equal amount of fresh medium. The samples obtained each time were tested for the amount of CBD released from the drug-loaded nanomicelles according to chromatographic conditions, and the cumulative release rate of CBD at different time points was calculated. The release curve was drawn with the cumulative release rate of CBD as the ordinate and the in vitro drug release time as the abscissa. The cumulative release rate of CBD was calculated using the following formula.
[0222]
[0223] Where, Er: cumulative release of CBD; Ve: volume of replacement buffer; V 0 : total volume of release medium; C i: The concentration of the sample at the i-th sampling, i = 1, ..., n-1; m CBD : CBD mass in drug-loaded nanomicelles; n: number of times of replacing buffer; C n : The concentration of the sample at the nth sampling.
[0224] The results are as follows Fig.18 As shown in the figure, the cumulative release rates of CBD / CCMC for 144h were 21.83% (pH=7.4) and 37.71% (pH=5.5), respectively. This may be because as the pH value of the solution gradually decreases, the CBD / CCMC nano-micelle system disintegrates, and the amide bond is rapidly hydrolyzed, thereby accelerating the release of cannabidiol. The cannabidiol nano-micelles all showed good sustained release performance, and the burst release phenomenon was not obvious, indicating that the drug was basically embedded in the nano-micelles and combined with hydrophobic forces. With the gradual dissolution and degradation of the carrier material, cannabidiol was continuously released at a relatively slow rate. Under different pH conditions, the drug release rate was different, indicating that the release of drugs in nano-micelles was pH-dependent.
[0225] Example 5: Study on oral absorption and anti-inflammatory mechanism of CBD / CCMC drug-loaded nanomicelles
[0226] The CBD / CCMC drug-loaded nanomicelles used in this example were prepared according to the optimal preparation process parameters in “(4) Orthogonal experiment and results” in Example 4, and the method in “(1) Preparation of CBD / CCMC drug-loaded nanomicelles” in Example 4; the CCMC blank nanomicelles used in this example were prepared according to the preparation method in “Step (i)” under “(1) Preparation of CBD / CCMC drug-loaded nanomicelles” in Example 4.
[0227] The PBS buffer used in this example has a pH of 7.2-7.4 and a concentration of 0.01M.
[0228] 1. Experimental methods
[0229] 1.1 Cell culture
[0230] Caco-2 cells were cultured in MEM medium containing fetal bovine serum (FBS, 10%), penicillin-streptomycin double antibody solution (100 U·mL -1 )-Streptomysin (100 μg mL -1 ), 5v / v%CO at 37°C and 95% humidity 2 The cells were cultured in a constant temperature incubator. 2) in a culture flask until the cells grow to a density of more than 90%, and then digest them with 0.25% trypsin-0.2% EDTA solution at a ratio of 1:2 or 1:3 before passage.
[0231] 1.2. Determination of safe drug concentration
[0232] 1.2.1 CCK-8 experiment
[0233] The CCK-8 method was used to investigate the effects of CCMC blank micelles, CBD and CBD / CCMC drug-loaded nanomicelles on the survival rate of Caco-2 cells. 5 Caco-2 cells were seeded in a 96-well plate at a density of 100 μL per well. 200 μL of PBS solution was seeded in the outer wells of the 96-well plate to provide a humid environment and cultured in a 37°C incubator. After the Caco-2 cells adhered to the wall, 10 μL of drug-containing MEM was added to each well to make the final concentration of CCMC blank micelles 0-1000 μg mL -1 The final concentration of CBD in CBD or CBD / CCMC drug-loaded nanomicelles was 2.5 μg mL -1 , 5μg·mL -1 , 7.5 μg·mL -1 , 10μg·mL -1 , 12.5 μg·mL -1 , 15μg·mL -1 The cells were grouped and treated with corresponding drugs. Each group had six replicate wells, and the control group had 6 wells (with cells, no drugs, and MEM culture medium). After incubation for 24 hours, 10 μL of CCK-8 solution was added to each well, and the cells were placed in a 37°C incubator for 1 hour. The absorbance (OD) value at a wavelength of 450 nm was detected using an ELISA reader and calculated according to the following formula: Cell survival rate (%) = OD 处理孔 / OD 对照孔 × 100%. 处理孔 Indicates the cell absorbance value after adding the drug, OD 对照孔 Indicates the cell absorbance value of the blank control.
[0234] Test results such as Fig. 20 As shown in the figure, the experimental results show that in order to verify the good biocompatibility of the polymer material, we used CCMC blank micelles to treat Caco-2 cells. The results show that CCMC blank micelles have a good biocompatibility in the range of 0 to 1000 μg mL -1 The cell survival rate did not change significantly at the concentration of CBD and CBD / CCMC loaded nanomicelles. -1The cell survival rate was greater than 90% within the experimental concentration range, indicating that CCMC blank micelles, CBD and CBD / CCMC did not cause damage to cells.
[0235] 1.2.2 LDH release detection
[0236] The lactate dehydrogenase (LDH) release method was used to investigate the effects of CCMC blank nanomicelles, CBD and CBD / CCMC loaded nanomicelles on the cell membrane integrity of Caco-2 cells. Caco-2 cell suspension was incubated at 1×10 5 The cells were inoculated at a density of 100 μL per well in a 96-well plate, and 200 μL of PBS solution was added to the outer wells of the 96-well plate to provide a humid environment. The cells were cultured in a 37°C incubator. After the Caco-2 cells attached to the wall, 10 μL of drug-containing MEM was added to each well to make the final concentration of CCMC blank nanomicelles 0-1000 μg·mL -1 The final concentrations of CBD in CBD or CBD / CCMC loaded nanomicelles were 2.5, 5, 7.5, 10, 12.5, and 15 μg mL -1 , with blank MEM as the control group. The cells were grouped and subjected to corresponding drug interventions, with six replicate wells in each group. After incubation for 24 hours, 20 μL of the supernatant from each well was taken out and added to another new 96-well plate, and the reagent solution was added according to the requirements of the LDH release kit. Then, the absorbance (OD) value at a wavelength of 570 nm was detected using an ELISA instrument and calculated as follows: Cell membrane integrity (%) = OD 处理孔 / OD 对照孔 × 100%. 处理孔 Represents the absorbance value of the cell supernatant after drug treatment, OD 对照孔 It represents the absorbance value of the blank control cell supernatant.
[0237] Test results such as Fig.21 As shown in the experimental results, the blank micelle concentration of CCMC is 0~1000μg·mL -1 The CBD concentration in CBD and CBD / CCMC drug-loaded nanomicelles was 0-15 μg·mL -1 In the range of , the release amount of LDH did not change significantly, indicating that CCMC blank micelles, CBD and CBD / CCMC did not destroy the integrity of the cell membrane within the experimental concentration range.
[0238] 1.3 Establishment and characterization of Caco-2 cell monolayer model
[0239] 1.3.1 Establishment of Caco-2 cell monolayer model
[0240] Cells were cultured at 1 × 10 per ml 5Cells were inoculated into the Transwell chamber at a density of 100 cells / mL. 0.5 mL of cell suspension was added to the apical side (AP) and 1.5 mL of complete culture medium (MEM culture medium in "1.1, Cell Culture") was added to the basal side (BL). The medium was changed every two days in the first week after inoculation, and every day thereafter, and cultured until 21 days.
[0241] 1.3.2 Characterization of the Caco-2 Cell Monolayer Model
[0242] 1.3.2.1 Microscopic observation
[0243] The status of Caco-2 cells at different growth stages in the Transwell chamber was observed under a microscope. Fig. 22 shown.
[0244] 1.3.2.2 Transephrine electrical resistance (TEER) detection
[0245] Caco-2 cells were inoculated in the Transwell chamber according to the above method, and the TEER of different cell growth times was measured using a resistance meter ERS. Before the measurement, the electrode was sterilized by soaking in 70% ethanol for 15 to 20 minutes, air-dried in the air for 15 seconds, and then placed in a PBS solution for 15 minutes. Then the electrode was vertically inserted into the culture well, and the end of the electrode could not touch the bottom of the chamber. Three points were randomly selected in each well for 3 times. The measured value of the experimental group inoculated with Caco-2 cells was recorded as R, and the measured value of the blank group without Caco-2 cells was recorded as R o , calculate the actual resistance value of each hole according to the formula: TEER = (R t -R o )×A(Ω·cm 2 ). Where R t is the measured value of the experimental group inoculated with Caco-2 cells, R o is the measurement value of the blank group without inoculation of Caco-2 cells, and A is the area of the Transwell membrane.
[0246] The results are as follows Fig.23 As shown in the figure, the experimental results show that the TEER of the Caco-2 cell model established in this experiment increases with the extension of culture time, indicating that the tightness gradually increases with the extension of culture time. The TEER value reaches 800Ω·cm in the second week of culture. 2 By 21 days, the TEER value tended to be stable, indicating that a complete and tight cell monolayer was formed.
[0247] 1.3.2.3. Alkaline phosphatase activity assay
[0248] The ALP / AKP kit was used to measure the activity of ALP in the Caco-2 cell monolayer and evaluate the growth and differentiation characteristics of Caco-2 cells. ALP can decompose disodium phenyl phosphate, and the free phenol produced reacts with 4-aminoantipyrine in an alkaline solution and is oxidized by potassium ferrocyanide to form a red internal derivative. The enzyme activity can be determined based on the depth of red. The culture fluid in the culture dish (n=3) was used as a sample, and then the activity of ALP in the cell fluid was detected according to the instructions in the ALP / AKP kit.
[0249] The results are as follows Fig.24 As shown, the experimental results showed that: the results of ALP activity detection found that the ALP activity ratios of the AP side and the BL side at the 3rd, 7th, 14th and 21st days were 1.02±0.02, 1.78±0.12, 2.97±0.21, and 4.23±0.09, respectively, indicating that when the Caco-2 cells were cultured to 21 days, the distribution of alkaline phosphatase was very asymmetric, most of the enzyme was on the brush border side, and the Caco-2 cell model had polar characteristics.
[0250] 1.3.2.4. Fluorescein sodium transmittance test
[0251] Prepare 100 μg mL -1 The fluorescein sodium stock solution was diluted to the following concentrations: 0, 1, 5, 10, 20, 100 μg mL -1 After the Transwell plate was plated for 21 days, one experimental well was randomly selected from each plate as the fluorescein sodium transport well. The control group was the well without cells. The culture medium in the upper and lower chambers of the wells was removed, and an appropriate amount of sterile PBS solution was added for rinsing. The solution in the fluorescein sodium transport well was removed, and 0.5 mL of 100 μg mL was added to the upper chamber of the well. -1 1.5 mL of fluorescein sodium solution was added to the lower chamber and placed in a 37°C constant temperature CO 2 The cells were cultured in a cell culture incubator for 0.5, 1, 1.5, 2, and 2.5 h. The absorbance of the samples was measured at 490 nm using an ELISA reader. A standard curve was drawn and the transmittance of sodium fluorescein in each well was calculated.
[0252] Fluorescein sodium is highly water-soluble and can be transported from the intercellular space, so it can be used to detect the integrity of the cell monolayer. Fig.25 As shown, Fig.25 As shown in the figure, the permeability of sodium fluorescein gradually increased within 0 to 2.5 hours after sodium fluorescein was applied to the Caco-2 cell model. Compared with the control group, the permeability of sodium fluorescein in the experimental group was significantly reduced and increased slowly. The results showed that the density and integrity of the Caco-2 cell model were good, which met the requirements of the transport experiment.
[0253] 1.4. CBD content determination in Caco-2 cells and rat plasma
[0254] 1.4.1. Sample processing method
[0255] Cell sample processing: Take 100 μL of cell sample, add 300 μL of methanol to precipitate protein, vortex and place for 30 minutes, centrifuge at 12000 rpm for 20 minutes, and take the supernatant for sampling.
[0256] Plasma sample processing: Take 100 μL of plasma, add 5 μL of 70% methanol and internal standard working solution (10 ng mL -1 Diphenhydramine) 5 μL, acetonitrile 100 μL and methyl tert-butyl ether 400 μL, vortex for 1 min, centrifuge at 12000 rpm for 10 min, blow dry the upper liquid with nitrogen. The residue was re-dissolved with 70% methanol 100 μL, centrifuged at 12000 rpm for 10 min, and the supernatant was sampled.
[0257] 1.4.2 Chromatographic conditions
[0258] CBD detection method in Caco-2 cells: Chromatographic conditions: Chromatographic column: Agilent Eclipse XDB-C18 (250 mm × 4.6 mm, 5 μm); Mobile phase: acetonitrile: 0.1 wt% formic acid = 80:20; Detection wavelength: 210 nm, column temperature: 30.0 °C, flow rate: 1.0 mL min -1 , injection volume: 20μL, detection time: 20min, isocratic elution.
[0259] Detection method of CBD in plasma: Chromatographic conditions are: chromatographic column: CORTECS C18 Column (150mm×4.6mm, 2.7μm), mobile phase A: 0.1wt% formic acid-water, mobile phase B: acetonitrile; gradient elution: 0~2min, A:B=30:70; 2~9min, A:B=10:90; 9.1~16min, A:B=30:70; detection wavelength: 210nm, column temperature: 30.0℃, flow rate: 0.3mL / min, injection volume: 5μL.
[0260] The mass spectrometry conditions used were: ion source: ESI source; detection mode: full ion detection; scanning mode: multiple reaction monitoring (MRM).
[0261] Mass spectrometry detection ions and parameters: cannabidiol, detection range is 315.2-316.2 m / z, declustering voltage is 97.6 V, and collision voltage is 31.9 V; diphenhydramine, detection range is 255.2-257.3 m / z, declustering voltage is 97.6 V, and collision voltage is 31.9 V.
[0262] 1.4.3. Standard curve drawing
[0263] Cells: Accurately weigh the CBD reference substance and dissolve the blank cell suspension to a concentration of 500 μg mL -1 The stock solution was diluted with PBS buffer in the following concentration gradients: 0.5, 1, 3, 6, 15, 30, 50, 100 μg mL -1 After processing according to the "Cell Sample Processing" method under "1.4.1. Sample Processing Method", the sample was injected according to the "CBD Detection Method in Caco-2 Cells" in "1.4.2. Chromatographic Conditions". The peak area of the analyte was used as the ordinate and the concentration of the analyte was used as the abscissa. A linear regression was performed and the regression equation was Y=99884X-15221, R 2 =0.9998, good linear relationship.
[0264] Plasma: Take 100 μL of blank mouse plasma and add 10 μL of CBD methanol solution of different concentrations to prepare CBD concentrations of 10, 20, 40, 100, 200 and 400 ng·mL -1 The series of solutions were treated according to the "Plasma Sample Treatment" under "1.4.1. Sample Treatment Method", and then determined using the "Plasma CBD Detection Method" under "1.4.2. Chromatographic Conditions". The standard curve was drawn with the concentration of CBD reference substance in plasma as the abscissa and the peak area ratio of CBD and diphenhydramine as the ordinate. The regression equation was calculated to be Y=0.01812X+0.44521, R 2 =0.9991, good linear relationship.
[0265] 1.5. Study on the uptake characteristics of CBD / CCMC nanomicelles
[0266] 1.5.1 Effect of time on Caco-2 cell uptake characteristics
[0267] Caco-2 cells (obtained from "1.1, Cell culture") were cultured at 1×10 5 pc·mL -1 The cells were inoculated at a high density in a 6-well plate, and the medium was changed every other day. After one week, the medium was changed every day. After culturing for 14 days, the PBS solution was gently washed three times and then discarded. -12mL of PBS solution of CBD or CBD / CCMC drug-loaded nanomicelles was added and cultured in an incubator at 37°C for 0.5, 1.0, 1.5, 2, 2.5, and 3h, respectively, with 3 wells at each time point. After the incubation, the drug-containing buffer was discarded, and pre-cooled PBS was added to terminate cell uptake, and the cell monolayer was quickly rinsed 3 times. 200μL of cell lysis solution was added to each well, and the cells were lysed on ice for 5min. The cells were scraped into Ep tubes with a cell scraper and ultrasonically crushed. After taking a portion according to the "Cell Sample Processing" under "1.4.1, Sample Processing Method", the CBD content was determined by HPLC ("CBD Detection Method in Caco-2 Cells" in "1.4.2, Chromatographic Conditions"). The concentration of CBD in the cells of each well sample was divided by the standardized data of total protein in each well, expressed in μg / mg protein.
[0268] 1.5.2 Effect of concentration on Caco-2 cell uptake characteristics
[0269] The cell treatment was the same as in 1.5.1, with the concentrations of 2.5, 5, 7.5, 10, 12.5, and 15 μg mL -1 PBS solution of CBD or CBD / CCMC drug-loaded nanomicelles was added to the cells, 2 mL per well, 3 wells per concentration in parallel, and cultured in a 37°C incubator for 4 hours. After the end, the drug-containing buffer was discarded, pre-cooled PBS was added to terminate cell uptake, and the cell monolayer was quickly washed 3 times. Other steps are the same as 1.5.1.
[0270] 1.5.3 Effect of temperature on Caco-2 cell uptake characteristics
[0271] The cell treatment was the same as in 1.5.1, except that 15 μg mL -1 2 mL of PBS solution of CBD or CBD / CCMC drug-loaded nanomicelles was placed in an environment of 4°C and 37°C for incubation for 1.5 h, with 3 wells at each temperature. After the incubation, the drug-containing buffer was discarded, pre-cooled PBS was added to terminate cell uptake, and the cell monolayer was quickly rinsed 3 times. Other steps were the same as 1.5.1.
[0272] 1.5.4 Effects of endocytosis inhibitors on Caco-2 cell uptake characteristics
[0273] The cell treatment was the same as in 1.5.1, except that 15 μg mL -1 2 mL of PBS solution of CBD or CBD / CCMC drug-loaded nanomicelles was added with MEM (Control group), 10 mmol·L -1 of MβCD and 10 μg mL -13 mL of Chlorpromazine was placed in an environment of 37°C for 1 hour, with 3 wells set at each temperature. After the incubation, the drug-containing buffer was discarded, pre-cooled PBS was added to terminate cell uptake, and the cell monolayer was quickly rinsed 3 times. Other steps are the same as 1.5.1.
[0274] For detailed data, please see Fig.26 The experimental results showed that the drug concentration was 15 μg·mL -1 During the period of 0-3h, the uptake of CBD and CBD / CCMC in Caco-2 cells first increased with time and then reached saturation, reaching the maximum at 2h. The results showed that the maximum uptake time of CBD and CBD / CCMC in Caco-2 cells was 2h, which will be the time point for subsequent uptake experiments ( Fig.26 A). At 2 h, the uptake of CBD and CBD / CCMC in Caco-2 cells increased with the increase of concentration, and there was no saturation phenomenon; at the same concentration, the uptake of CBD / CCMC group was significantly higher than that of CBD group, suggesting that CBD and CBD / CCMC uptake may not require a carrier and belong to concentration-dependent passive diffusion or endocytosis ( Fig.26 B). The uptake of CBD and CBD / CCMC in Caco-2 cells increased significantly with increasing temperature, indicating that the uptake of CBD and CBD / CCMC in cells is energy-dependent and may be an active uptake or endocytosis method ( Fig.26 C). Compared with the blank group, after adding the endocytosis inhibitor MβCD or Chlorpromazine, the uptake of CBD in cells decreased, and the uptake of CBD / CCMC decreased significantly, indicating that endocytosis is involved in the uptake of CBD and CBD / CCMC in cells ( Fig.26 D).
[0275] 1.6 Bilateral transport experiment of CBD / CCMC nanomicelles in Caco-2 cell monolayer model
[0276] 1.6.1. Study on the transport efficiency of CBD / CCMC nanomicelles in Caco-2 cell monolayer model
[0277] Select a Caco-2 cell monolayer model that meets the transport requirements (prepared in "1.3.1, Establishment of Caco-2 cell monolayer model"). Replace the cell culture medium with a blank PBS solution at 37°C, culture the cells in the Transwell plate for 30 minutes, and gently rinse the Transwell membrane with a pipette to remove impurities on the cell surface. Transport from AP to BL: Add 15 μg mL -10.5 mL of PBS solution of CBD or CBD / CCMC nanomicelles was added to the BL side, and 1.5 mL of blank PBS solution was added to the BL side. The mixture was incubated in a constant temperature oscillator at 37 °C. 100 μL of samples were collected from the lower layer at 30, 60, 90, and 120 min, and the same volume of blank PBS solution was added. Transport from BL to AP: 15 μg mL -1 1.5 mL of PBS solution of CBD or CBD / CCMC nanomicelles was added, 0.5 mL of blank PBS solution was added to the AP side, and incubated in a constant temperature oscillator at 37 ° C. 100 μL of the upper layer of the side without CBD or CBD / (γ-PGA-g-CHOL) was sampled at 30, 60, 90, and 120 min, and the same volume of blank PBS solution was added. 300 μL of methanol was added to the sample, vortexed for 1 min, left for 30 min, centrifuged at 15000 rpm for 15 min, and 20 μL was taken for sample injection and measurement (sample injection and measurement according to the "CBD detection method in Caco-2 cells" in the "1.4.2, chromatographic conditions" item), and Papp (cm / s) and ER were calculated according to the following formula:
[0278]
[0279]
[0280] Where A is the permeable membrane area, here it is the bottom area of the donor pool Transwel1 membrane; C 0 is the initial drug concentration; dQ / dt is the drug transport amount per unit time; P app(B→A) indicates P transported from the BL side to the AP side of the Transwell membrane app Value; P app(A→B) It represents the Papp value of transport from the AP side to the BL side of the Transwell membrane.
[0281] 1.6.2. Study on the transport mechanism of CBD / CCMC nanomicelles in Caco-2 cell monolayer model
[0282] The effects of P-glycoprotein (P-gp) inhibitor verapamil (Ver), multidrug resistance-associated protein 2 (MRP2) inhibitor MK-571, and breast cancer resistance-associated protein (BCRP) inhibitor KO-143 were used to further investigate the effects of efflux protein inhibitors on the transport of CBD and CBD / CCMC nanomicelles. The effects of CBD and CBD / CCMC nanomicelles on the expression of P-gp, MRP2, and BCRP efflux proteins were investigated by Western blotting, and the transport mechanism of CBD and CBD / CCMC nanomicelles in the Caco-2 cell model was preliminarily elucidated.
[0283] The experimental steps are the same as those in "1.6.1", except that: AP→BL transport: 15 μg·mL -1 0.5 mL of PBS solution of CBD or CBD / CCMC, CBD or CBD / CCMC+45.5 μg / mL Ver, CBD or CBD / CCMC+26.9 μg / mL MK-571, CBD or CBD / CCMC+4.7 μg / mL KO-143 was added to the BL side, and 1.5 mL of blank PBS solution was added to the BL side. Similarly, for BL→AP transport: 15 μg·mL -1 1.5 mL of PBS solution of CBD or CBD / CCMC, CBD or CBD / CCMC+45.5 μg / mL Ver, CBD or CBD / CCMC+26.9 μg / mL MK-571, CBD or CBD / CCMC+4.7 μg / mL KO-143 was added, and 0.5 mL of blank PBS solution was added to the AP side. After incubation at 37°C for 2 hours, samples were collected from the side without drug addition. After sampling, the apparent permeability coefficient (Papp) and efflux rate (ER) were calculated according to the formula to investigate the effect of efflux protein inhibitors on the transport of CBD and CBD / CCMC.
[0284] The experimental results are shown in Table 18. The experimental results show that compared with the CBD group, the P app(A→B) , P app(B→A) There was no significant change in the ER and CBD transport, indicating that the transport of CBD may not be related to P-gp. app(A→B) Significantly increased, P app(B→A) The results showed that CBD may be the substrate of efflux proteins MRP2 and BCRP, and the transport of CBD was affected by MRP2 and BCRP. Compared with the CBD / CCMC group, the P app(A→B) , P app(B→A) There is no significant change in ER and P after adding Ver app(A→B) Increase, P app(B→A) The results showed that the transport of CBD / CCMC was affected by P-gp. Compared with the CBD group, CBD / CCMC was not affected by MRP2 and BCRP, which means that CBD / CCMC may avoid the efflux of efflux proteins MRP2 and BCRP to increase the transport of drugs.
[0285] Table 18 Results of bilateral transport experiments of CBD and CBD / CCMC nanomicelles in the Caco-2 cell monolayer model
[0286]
[0287] “*” indicates that the results were significantly different from those in the CBD group, and “#” indicates that the results were significantly different from those in the CBD / CCMC group.
[0288] 1.7. Pharmacokinetic study of CBD and CBD / CCMC nanomicelles
[0289] Twelve SD male rats were gavaged (100 mg / kg) with CBD or CBD / CCMC nano-micelles, and about 100 μL of blood was collected from the eye sockets at 0.5, 1, 1.25, 1.5, 1.75, 2, 4, 8, 24 and 48 hours. The blood was placed in a heparin anticoagulation centrifuge tube and centrifuged at 6000 rpm for 5 minutes. The sample was transferred to a polypropylene tube and stored at -80 ° C for testing. The obtained sample was treated according to the "Plasma Sample Treatment" method under "1.4.1, Sample Treatment Method", and then measured according to the conditions under "CBD Detection Method in Plasma" under "1.4.2, Chromatographic Conditions".
[0290] The research results are as follows Fig. 27 As shown, the experimental results show that compared with free CBD, the area under the drug-time curve of CBD / CCMC nanomicelles increases, the average residence time increases, and the clearance rate decreases, indicating that CBD / CCMC nanomicelles can prolong the in vivo circulation time of CBD and slow down the clearance rate.
[0291] 1.8. Study on the anti-inflammatory activity of CBD and CBD / CCMC nanomicelles
[0292] 1.8.1 LPS concentration screening
[0293] According to the experimental design, it was divided into 6 experimental groups: 0, 0.1, 1, 10, 25, and 50 μg·mL -1 LPS. Caco-2 cells grown to the logarithmic phase (obtained from the culture in "1.1, Cell culture") were digested and centrifuged, and 1×10 5 Cells were inoculated into 96-well plates at a cell density of 100 μL per well. After the cells adhered to the plate for 24 h, 100 μL of culture medium with LPS was added to the 6 experimental groups. No LPS was added to the control group (Control group). The culture bottles were placed in an incubator and cultured for 24 h before cck-8 and LDH release detection.
[0294] Test results see Fig.28 The experimental results showed that CCK-8 and LDH detection revealed that 1 μg·mL -1 LPS had no effect on cell viability. When the LPS concentration was ≥10 μg·mL -1 When the cell viability decreased significantly, the cell membrane damage became more serious. The secretion level of inflammatory factors was detected by ELISA method. The results showed that 0-10 μg mL -1After LPS intervention, inflammatory factors IL-8, IL-1β, and TNF-α increased significantly. -1 , the level of cellular inflammatory factors tends to be stable. After comprehensive consideration, 10 μg·mL was selected -1 As the experimental concentration of LPS.
[0295] 1.8.2 Establishment of cellular inflammation model and experimental grouping
[0296] This study was divided into a normal control group, a model group (LPS group), and an experimental group (LPS+CBD group, LPS+CBD / CCMC nanomicelle group). Based on the established Caco-2 cell transport model, the model group and the experimental group were cultured with MEM medium (10 μg mL -1 LPS was treated with cells for 24 h to prepare the cell inflammation model; the normal control group was cultured with ordinary cell culture medium. The experimental groups were added with final concentrations of 5, 10, and 15 μg mL -1 CBD or CBD / CCMC, and equal volumes of PBS solution were added to the model group and the control group.
[0297] 1.8.3. Anti-inflammatory activity test of CBD and CBD / CCMC nanomicelles
[0298] The anti-inflammatory activity of CBD and CBD / CCMC nanomicelles was compared by detecting cell viability and transmembrane resistance. The cell viability and transmembrane resistance were detected by CCK-8 method and LDH release method, and the detection method was the same as "1.3.2.2, transmembrane resistance (TEER) detection" above.
[0299] Test results see Fig.29 , Fig.30 The experimental results showed that LPS was used to induce inflammatory damage in Caco-2 cells. The results showed that after adding CBD and CBD / CCMC loaded nano-micelles for intervention, compared with the LPS stimulation group, the addition of CBD could significantly increase the cell survival rate and reduce the LDH activity, indicating that CBD and CBD / CCMC loaded nano-micelles can inhibit LPS-induced Caco-2 cell inflammatory damage and have good anti-inflammatory activity ( Fig.29). The results of transmembrane resistance measurement of Caco-2 cell model showed that compared with the blank control group, the TEER value of LPS-induced Caco-2 monolayer cell model in the model group decreased rapidly within 0-5h and tended to stabilize after 8h; compared with the LPS group, the TEER value of Caco-2 cell model was significantly increased after 5h of CBD and CBD / CCMC drug-loaded nanomicelles administration, and the increase effect of CBD / CCMC drug-loaded nanomicelles group was more significant, indicating that CBD and CBD / CCMC drug-loaded nanomicelles can increase its transmembrane resistance, reduce intestinal permeability, and improve LPS-induced Caco-2 cell model barrier function damage, and the anti-inflammatory effect of CBD / CCMC drug-loaded nanomicelles group is better than that of CBD group, and this ability is concentration-dependent ( Fig.30 ).
[0300] 1.8.4 Research on the anti-inflammatory mechanism of CBD
[0301] Detection of the secretion and expression of cellular inflammatory factors and tight junction proteins: After the cells (obtained by culture in "1.1, cell culture") were inoculated into the culture plate and treated according to the experimental grouping in "1.8.2", the cell culture supernatant was collected at 4°C. Take an appropriate amount of culture supernatant and detect the secretion level of cellular inflammatory factors such as IL-1β, IL-8, TNF-α according to the instructions of the ELISA assay kit. Western Blotting was used to detect the expression level of tight junction proteins such as ZO-1, and the anti-inflammatory mechanism of CBD and CBD / CCMC nano-micelles was preliminarily clarified.
[0302] Test results see Fig.31 The experimental results showed that compared with the normal control group, the secretion of IL-8, IL-1β, and TNF-α in the LPS group was significantly increased, causing inflammatory damage; compared with the LPS group, different concentrations of CBD and CBD / CCMC could reduce the secretion levels of IL-8, IL-1β, and TNF-α, and CBD / CCMC had a more significant inhibitory effect on cellular inflammatory factors, indicating that CBD and CBD / CCMC can relieve inflammatory responses by regulating the secretion levels of cellular inflammatory factors, and CBD / CCMC has better anti-inflammatory activity.
[0303] The present invention provides O-carboxymethyl chitosan-g-cholesterol succinate monoester and its preparation method and application ideas and methods. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.
Claims
1. Application of O-carboxymethyl chitosan-g-cholesterol succinate monoester in the preparation of cannabidiol-loaded drug-loaded nanomicelles, wherein the O-carboxymethyl chitosan-g-cholesterol succinate monoester is prepared according to the following preparation method: (1) Cholesterol, 4-dimethylaminopyridine and succinic anhydride are dissolved in dichloromethane and subjected to esterification reaction under the protection of inert gas to obtain cholesterol succinate monoester, denoted as CHS; (2) dissolving O-carboxymethyl chitosan in water to obtain a first mixed solution; dissolving CHS obtained in step (1) in N,N-dimethylformamide to obtain a second mixed solution; adding 1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride and N-hydroxysuccinimide to the second mixed solution for activation reaction to obtain an activation solution; adding the activation solution to the first mixed solution for coupling reaction; after the reaction is completed, centrifuging the reaction solution, dialyzing the supernatant, and freeze-drying the dialyzate to obtain O-carboxymethyl chitosan-g-cholesterol succinate, denoted as CCMC; The application of O-carboxymethyl chitosan-g-cholesteryl succinate monoester in preparing cannabidiol-loaded drug-loaded nano micelles comprises the following steps: (i) mixing the O-carboxymethyl chitosan-g-cholesterol succinate monoester with water to obtain an amphiphilic polymer mixed solution; stirring the amphiphilic polymer mixed solution at room temperature for 8 to 24 hours, and then subjecting the mixed solution to ultrasonic treatment under ice bath conditions; after the ultrasonic treatment, centrifuging, filtering, and freeze-drying the mixed solution to obtain amphiphilic polymer blank micelles; (ii) dissolving cannabidiol in tetrahydrofuran to obtain a cannabidiol solution; dissolving the amphiphilic polymer blank micelles obtained in step (i) in deionized water to obtain an amphiphilic polymer blank micelle aqueous solution; adding the cannabidiol solution to the amphiphilic polymer blank micelle aqueous solution, stirring at 300-400 rpm at room temperature for 8-10 h, and after the stirring is completed, placing the reaction solution in a dialysis bag for dialysis, filtering the obtained dialyzate, and freeze-drying to obtain cannabidiol-loaded drug nanomicelles.
2. The use according to claim 1, characterized in that: In step (1), the molar ratio of cholesterol to 4-dimethylaminopyridine and succinic anhydride is 1:1:2; the esterification reaction is carried out at room temperature and for 16 to 32 hours; and the inert gas is nitrogen.
3. The use according to claim 1, characterized in that: In step (2), the concentration of O-carboxymethyl chitosan in the first mixed solution is 5-20 mg•mL -1 ; The concentration of CHS in the second mixed solution is 10~12 mg•mL -1 ; The mass ratio of O-carboxymethyl chitosan to CHS is 1~2:1; the molar ratio of CHS to 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:1.5:1.5; the activation reaction has a reaction temperature of room temperature and an activation time of 60~100 min; the coupling reaction has a reaction temperature of 60~90°C and a reaction time of 36~54 h.
4. The use according to claim 1, characterized in that: In step (i), the concentration of O-carboxymethyl chitosan-g-cholesterol succinate in the amphiphilic polymer mixture is 0.025-0.5 mg•mL -1 ; The probe is ultrasonically treated with an ultrasonic power of 250~400 W and an ultrasonic time of 5~9 min.
5. The use according to claim 1, characterized in that: In step (i), the amphiphilic polymer blank micelles have an average particle size of 173.9±2.3 nm and a Zeta potential of -17.6±1.3 mV.
6. The use according to claim 1, characterized in that: In step (ii), the concentration of cannabidiol in the cannabidiol solution is 3-4 mg•mL -1 The concentration of the blank micelles of the amphiphilic polymer in the blank micelle aqueous solution is 3-5 mg•mL -1 ; The volume ratio of tetrahydrofuran in the cannabidiol solution to deionized water in the amphiphilic polymer blank micelle aqueous solution is 1:5~7.
7. The use according to claim 1, characterized in that: In step (ii), the cannabidiol-loaded nanomicelles have an average particle size of 230.6±1.8 nm, a PDI of 0.170±0.053, and a Zeta potential of -13.5±1.2 mV.
Citation Information
Patent Citations
Cannabidiol-loaded nano-micelle and preparation method and application thereof
CN113712916A